Performance analysis of cocoa certification program in Polewali Mandar Regency - Herman, Fitriani; Arsyad, Muhammad; Karim, Ikawati; Nurlaela, Nurlaela (Anjoro: International Journal of Agriculture and Business, 2020)
One of the agricultural development income is through agribusiness activities oriented to increasing competitiveness and sustainable economic development of the community, which is carried out within the framework of autonomy to strengthen the regional economy. Cocoa is a strategic commodity in case, firstly, Indonesia is the number two cocoa producer in the world after Ivory Coast, with production of 809,586 tons in 2012. In 2012, this commodity has contributed foreign exchange of US $ 1.1 billion, which is the third foreign exchange earnings spread after oil palm and rubber. Secondly, this product involves 95% of smallholder farmers with increased land ownership of 0.5-2 ha. Thus, the development of the cocoa business will directly or indirectly affect the microeconomics. This study aims to determine the performance and the level of satisfaction of the cocoa certification program in one of cocoa production center in Polewali Mandar. This study uses Importance Performance Analysis (IPA). The results of this study indicate that the achievement of the performance of the cocoa certification program has been running quite well, but there are still some that have not worked optimally where the level of satisfaction of the cocoa certification program that 78.03% are satisfied with the program's performance cocoa certification and 21.97% farmers were not satisfied with the performance of the cocoa certification program carried out in Polewali Mandar.